2006
DOI: 10.1007/s00403-006-0653-5
|View full text |Cite
|
Sign up to set email alerts
|

A large preclinical animal model to assess ex vivo skin gene therapy applications

Abstract: Because of its easy accessibility, the skin is a very attractive target for gene therapy purposes. To study potential clinical applications in a preclinical setting, appropriate animal models are needed. Pig skin is very similar to human skin, and a variety of human diseases that are potentially amenable to gene therapy applications also occur in pigs. Only a few studies have analyzed the engraftment of transduced keratinocytes (KC) in pigs, however, with limited success. We describe a porcine model in which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…T he skin is the largest organ of the body and plays several vital functions such as protection against environmental aggressions (biologic, physical or chemical), thermoregulation, metabolism and sensation. Porcine skin has been widely employed as a substitute for human skin in various fields of dermatological research because of several anatomical and physiological similarities with human skin [1][2][3][4][5][6][7]. As in humans, porcine skin is divided into three layers, i.e.…”
mentioning
confidence: 99%
“…T he skin is the largest organ of the body and plays several vital functions such as protection against environmental aggressions (biologic, physical or chemical), thermoregulation, metabolism and sensation. Porcine skin has been widely employed as a substitute for human skin in various fields of dermatological research because of several anatomical and physiological similarities with human skin [1][2][3][4][5][6][7]. As in humans, porcine skin is divided into three layers, i.e.…”
mentioning
confidence: 99%
“…By retrospectively studying rejection in a large number of VCA transplants in MGH minipigs, we have proposed new, more refined rejection criteria specific to the MGH minipig, based on the original Banff criteria. Although we have highlighted many aspects of the striking similarity of pig skin anatomy and healing compared with that of human skin, 10-18 pigs are different than humans both in their behavior and in some aspects of their inflammatory response. Pigs are more likely to traumatize skin posttransplantation, so small superficial pustules are not uncommon incidental findings.…”
Section: Discussionmentioning
confidence: 97%
“…9 It is well established that swine skin is comparable to human skin in clinical and histopathological settings. 10-18 Anatomically, both pig and human skin have similar thickness ratios of dermis to epidermis, density of hair follicles, pigmentation (breed dependent), and dermal connective tissue composition. 18 Pig skin, like human skin, is also tightly adherent to the subcutaneous layer, in contrast to rodent skin.…”
Section: Introductionmentioning
confidence: 99%
“…In our case, to prepare the receiving bed covered by the cultured epidermal graft, we planned to use an electric dermatome, which is utilized in humans to harvest split‐thickness skin grafts (Goris and Nicolai, 1982; Jong and Lin, 1995; Sams et al., 2004). As trials of skin substitute grafting or gene therapy of skin disorders have been performed in pigs and immunodeficient nude mice, two species which have little to no hair; no trials in the dog, a hairy species, are currently found in the literature, to the author’s knowledge (Braye et al., 2001; Magnaldo and Sarasin, 2002; Pfützner et al., 2006). The aim of this study was to determine the depth of excision using a dermatome (Aesculap ® ) making it possible to export entire hair follicle bulbs from the bed of the future graft to achieve engraftment of the cultured epidermal sheet.…”
Section: Introductionmentioning
confidence: 99%